The Size And Costs Of Bribe Given And Solicited : Analyses Based On Convicted Offenders In Malaysia - Chong, Christine Siew Pyng (2017)
The main objectives of the study were to estimate the costs of bribe giving and soliciting, the factors affecting the size of bribes involved and to evaluate if penalties given out were correlated with bribe size. Annual data on convicted bribe givers and solicitors for a five year period (2010 to 2014) obtained from the Malaysian Anti-Corruption Commission were used. The findings suggested that bribe giving and soliciting would have cost the government a minimum revenue loss of RM23.9 million per year or the equivalent of 1.1 percent and 0.31 percent of the annual development funds allocated to health and education during this period, respectively.